Sources of mapping used in humanitarian emer- gencie: The case of Ebola - Martínez, José Antonio Barra; Morales-Yago, Francesco José; de Lázaro-Torres, María Luisa (Quaestiones Geographicae, 2022)
The need to rapidly respond to health emergencies has generated various institutional initiatives to identify their location, through mapping. This study employs a qualitative-exploratory method, based on the daily monitoring of eight Ebola epidemics between 2013 and 2021, to make an assessment of the usefulness of maps created specifically for Ebola. The results show that at least 14 organisations produce maps in the face of emergencies and epidemics such as Ebola. Consequently, it has been possible to design a search plan to aid in the monitoring of emergencies and to design an Ebola map with data obtained from these organisations and the initiatives they promote, which confirms the usefulness of these data sources and maps.